The Timeliness of the Botswana Parastatal Annual Report: 1994-1998 - Iwisi, Dominick S; Kitindi, Ernest G (The International Journal of Accounting and Business Society, 1999)
The corporate annual report is a common media employed by business entities to convey information to interested persons. An important component of the report are the ï¬nancial statements and the auditors report. Since the report is a primary source of information for shareholders, it is desirable that this informationis provided on a timely basis. The report should also be of quality desirable for meaningful decisions to be made. This study investigated the time it took parastatals in Botswana to have the annual report available. lt also embarked on establishing the quality of the accounts, as indicated by the auditorâ€™s opinion report. The results show that, on average, the Botswana parastatal required 5.35 months to avail the report. This compares unfavorably to other developed countries. However, compared to some other developing countries the results for Botswana parastatals are impressive. Key words: Timeliness, Annual reports, Parastatal, Audit reports